Limits on the reconstruction of a single dark energy scalar field potential from SNe Ia data - Piloyan, Arpine; Pavluchenko, Sergey A.; Amendola, Luca (Arxiv, 2018)
In this paper we perform a reconstruction of the scalar field potential responsible for cosmic acceleration using SNe Ia data. After describing the method, we test it with real SNe Ia data-Union2.1 and JLA SNe datasets. We demonstrate that with the current data precision level, the full reconstruction is not possible. We discuss the problems which arise during the reconstruction process and the ways to overcome them.